PROTOTYPE DOORSTOP WITH RFID SENSORS ARDUINO-BASED AS A VEHICLE SECURITY SYSTEM AT UNIVERSITIES - Muhammad Hanief; Luthfil Hadi Nugroho; Mia Galina (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
The rapid development of technology marks an advance in creating tools that can help people work, such as one of the technologies being developed by the author, namely Smart Parking technology using RFID (Frequency Radio Identification). RFID is a wireless technology for short-distance data transfer. The nature of RFID allows this technology to become an effective vehicle safety system. RFID technology can record incoming and outgoing data using a registered card. The author tried to implement and develop this RFID into a simple and easy-to-use security device. The tool will be tried in the experiment with two registered cards and one unregistered card 10 times each. The authors tried to test how accurate RFID readers were at reading registered cards. In addition to RFID, the authors also use ultrasonic sensors to detect passing vehicles. The test results showed that the RFID reader could function adequately and read with the right degree of accuracy and an average time of 0.6 seconds. In addition, the authors also included trials using barriers in RFID aimed at identifying the extent to which frequencies in RFID can work even if other objects still block them, the result being that RFID readers can still read cards registered at a distance of 1.5cm and barrier thicknesses of up to 2.0mm. In the trial period, the author felt quite satisfied with the results of the device's performance, but the author thought that the device could still be developed.